2009
DOI: 10.1093/carcin/bgp048
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signalling in breast cancer

Abstract: Breast cancer is the most common cause of cancer death among women worldwide. In order to improve the treatment of this disease, a more complete understanding of its biological basis is necessary. Since the Hedgehog (Hh) pathway was recently found to be required for growth and propagation of a number of different cancers, we discuss here the possible involvement of this pathway in the normal biology and development of cancer in the mammary gland. The use of mouse mammary cancer models has assisted the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
107
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 127 publications
0
107
0
Order By: Relevance
“…However, such a threshold hypothesis is not likely for morphogens that are expected to act in response to low gradients of ligand. More likely, the low activity of HH signaling in plaques must constitute inhibition downstream of the primary HH receptor Patched (7,9). Smoothened antagonists can inhibit HH signal transduction downstream of Patched and are thus obvious candidates to participate in the HH signaling dichotomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such a threshold hypothesis is not likely for morphogens that are expected to act in response to low gradients of ligand. More likely, the low activity of HH signaling in plaques must constitute inhibition downstream of the primary HH receptor Patched (7,9). Smoothened antagonists can inhibit HH signal transduction downstream of Patched and are thus obvious candidates to participate in the HH signaling dichotomy.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, LDLs contribute to plaque formation, but on the other hand, they contribute to plaque stability by carrying antagonists of downstream HH signaling. It is important, however, to point out that other mechanisms, such as suppressor of fused (SUFU) expression (7,34), may also contribute to the functional dichotomy in HH signaling in the human vasculature. Disregarding the exact mechanism of HH signal transduction inhibition in atherosclerotic plaques, it is tempting to suggest that this inhibition constitutes an important antipathogenic signal and that enhanced knowledge of the mechanisms involved may contribute to better treatment and prevention of atherosclerotic disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of activated Hh signaling in the development or progression of tumors remains to be elucidated. However, certain studies have indicated that Hh signaling plays a role in stem/progenitor cell maintenance and self-renewal, which is regarded as a significant marker of cancer stem cell (CSC) activation (19,20). Nevertheless, the role of this pathway in breast CSCs has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, published literature supports the potential for the involvement of particular aspects of the hedgehog/Gli signaling pathway in other types of solid human tumors [1116]. Here we will first address the nature of hedgehog signaling in normal and malignant cells and then describe the literature that suggests that hedgehog contributes to human prostate cancer.…”
mentioning
confidence: 95%